Psychological and situational profiles of social distance compliance during COVID-19. (2nd January 2022) - Haupt, Michael Robert; Weiss, Staci Meredith; Chiu, Michelle; Cuomo, Raphael; Chein, Jason M.; Mackey, Tim
ABSTRACT: Background: Health advice in the wake of the COVID-19 pandemic has called upon the public to re-evaluate risk associated with recently routine behavior. However, differences in demographics, situational circumstances, and psychological dispositions create inequities in how people are able to respond to risks presented by the virus. Method: Within a sample of 482 Americans, we examined the frequency of behavior reconceptualized as 'risky' by CDC public health guidelines released on 30 March 2020. We applied a cluster analysis using a data-driven persona framework from the field of user-design research, using only situational and dispositional (i.e. psychological) variables to identify profiles of individuals. Results: This profile approach unpacked important variability in the evaluation of risk for COVID-19 contagion, as well as adherence to public health guidance. Profiles engaged in high-risk behaviors were more likely required to work on-site and report higher financial impact related to the pandemic. Conclusion: Applying the profile approach facilitates personalized communications tailored to the psychological and situational circumstances of each profile that can promote compliance with public health guidelines and guide policy decisions. These results also suggest that risk-taking behaviors within the context of COVID-19 may also be driven by factors related to economic inequity since those who are more likely to be essential workers do not have the ability to remain as compliant to social distancing compared to those with higher economic status. Recommendations for policies promoting federally mandated paid leave policy in the US and employing qualitative methods for future research is discussed.